Kinetic field theory: non-linear cosmic power spectra in the mean-field approximation - Bartelmann, Matthias; Dombrowski, Johannes; Konrad, Sara; Kozlikin, Elena; Lilow, Robert; Littek, Carsten; Pixius, Christophe; Fabis, Felix (SciPost physics, 2021)
SciPost Journals Publication Detail SciPost Phys. 10, 153 (2021) Kinetic field theory: Non-linear cosmic power spectra in the mean-field approximation
Gesehen am 30.09.2021